2021
DOI: 10.33448/rsd-v10i9.18143
|View full text |Cite
|
Sign up to set email alerts
|

Prevalência de disfunções sexuais no puerpério de parto cesáreo

Abstract: Objetivo: Descrever a prevalência de disfunções sexuais no puerpério de parto Cesário. Metodologia: Estudo do tipo observacional descritivo, o tamanho da amostra foi de 30 puérperas. Sendo desenvolvido de forma digital, através de um formulário criado no Google Forms de outubro de 2020 a abril de 2021. A primeira etapa contou com o preenchimento dos dados sociodemográficos no formulário e em seguida aplicação do Female Sexual Function Index (FSFI), um autorrelato com 19 itens que abrange seis domínios sexuais … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
(4 reference statements)
0
1
0
Order By: Relevance
“…Regarding the FSFI domains, low values ranging between 4.74 and 3.36 with higher scores for satisfaction, pain (it is noteworthy that for the item pain are inverted values), orgasm and lubrication, and lower for desire and excitement. Baratella et al (2021) also reported lower scores for desire and arousal in relation to the other domains. However, these data are difficult to be compared since scores from other studies highlighted the importance of emotional and relational aspects for female sexual response.…”
Section: Discussionmentioning
confidence: 90%
“…Regarding the FSFI domains, low values ranging between 4.74 and 3.36 with higher scores for satisfaction, pain (it is noteworthy that for the item pain are inverted values), orgasm and lubrication, and lower for desire and excitement. Baratella et al (2021) also reported lower scores for desire and arousal in relation to the other domains. However, these data are difficult to be compared since scores from other studies highlighted the importance of emotional and relational aspects for female sexual response.…”
Section: Discussionmentioning
confidence: 90%